The Effect of Tax Arrears and Motor Vehicle Tax Revenue on Regional Revenue - Dody Faraitody Teguh; Astri Dwi Andriani; Muhamad Fikri Esa Putra Humaedi (MultiTech Publisher, 2022)
As the development of motorized vehicles advances every year, this should have an impact on tax revenues, but basically there is no influence from the increase in vehicles every year on tax revenues and motor vehicle tax arrears. Likewise, what happens in the Cianjur Regency area is that every year the number of vehicles increases, revenue should also increase and arrears decrease, basically the increase in vehicles every year has no impact on tax revenues and arrears in the Cianjur Regency area, even to the point that targets and realizations are not achieved. Motor vehicle tax receipts and arrears which affect regional income in the Cianjur Regency area. So with this the researcher aims to find out how big the influence of tax arrears and motor vehicle tax revenue is on regional income in the Cianjur Regency area. The method used is a descriptive associative quantitative method, and produces an influence of tax arrears and motor vehicle tax revenues on regional income in the Cianjur Regency area of 75.5%